2019
DOI: 10.1096/fj.201802681rr
|View full text |Cite
|
Sign up to set email alerts
|

The PPAR–microbiota–metabolic organ trilogy to fine‐tune physiology

Abstract: The human gut is colonized by commensal microorganisms, predominately bacteria that have coevolved in symbiosis with their host. The gut microbiota has been extensively studied in recent years, and many important findings on how it can regulate host metabolism have been unraveled. In healthy individuals, feeding timing and type of food can influence not only the composition but also the circadian oscillation of the gut microbiota. Host feeding habits thus influence the type of microbe‐derived metabolites produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 270 publications
(422 reference statements)
4
42
0
Order By: Relevance
“…These amino acids are precursors in the synthesis of the SCFAs, known to modulate obesity 113 and recognized PPAR agonists targeted to muscle. 85 Notably, butyrate is known to induce PGC-1α gene expression in skeletal muscleand adipose tissue as well as stimulates free fatty acid oxidation, 17 aligning with the results presented in this study. Enterocytes also use glutamate and aspartate as an energy source during epithelial layer renewal and nutrient absorption.…”
Section: Functional Profiles Of Pemf-and Exercise-conditioned Gut Msupporting
confidence: 87%
See 1 more Smart Citation
“…These amino acids are precursors in the synthesis of the SCFAs, known to modulate obesity 113 and recognized PPAR agonists targeted to muscle. 85 Notably, butyrate is known to induce PGC-1α gene expression in skeletal muscleand adipose tissue as well as stimulates free fatty acid oxidation, 17 aligning with the results presented in this study. Enterocytes also use glutamate and aspartate as an energy source during epithelial layer renewal and nutrient absorption.…”
Section: Functional Profiles Of Pemf-and Exercise-conditioned Gut Msupporting
confidence: 87%
“…On the contrary, longer-term endurance exercise 72 or PEMF exposure ( Figure 1C reinforcement in effect closes the loop between muscle (large activatable pool of mitochondria) and microbiome function. 85 Indeed, bidirectional communication between the gut microbiome and muscle mitochondria is now supported by numerous studies demonstrating that muscle mitochondria and the commensal gut microbiota cross talk (via the SCFAs that potentiate PGC-1α function) to modulate redox balance and systemic inflammation. 17,86,87 Adipose beiging is another accepted exercise adaptation that is likewise dependent on PGC-1α expression and associated changes in mitochondrial function and biogenesis.…”
mentioning
confidence: 99%
“…In particular, our study suggested that PPAR was positively correlated with the relative abundance of Faecalibacterium and negatively correlated with Blautia . Many literatures have reported that fatty acids can increase insulin sensitivity through the PPAR signaling pathway, thereby regulating blood glucose levels, which was closely related to the occurrence of GDM [6870]. In our study, there is a positive correlation between Faecalibacterium in stool and blood glucose levels, while Blautia is the opposite.…”
Section: Discussionsupporting
confidence: 58%
“…from the human gut, which produces high levels of butyric acid in vitro and is a net producer of acetate, had detectable butyrate kinase, acetate kinase, and butyryl-CoA:acetate-CoA transferase activities. Butyric acid is an important SCFA, and Oh et al (2019) demonstrated that SCFAs can activate the AMPK/PPAR pathway directly or by activating adipose tissue and can ultimately regulate fatty acid oxidation. Thus, Coprococcus sp.…”
Section: Discussionmentioning
confidence: 99%